Penyelesaian Perselisihan Hubungan Industrial yang Disebabkan oleh Hak Atas Upah Lembur di PT Tirta Investama Kabupaten Langkat Dihubungkan dengan UU No 2 Tahun 2004 - Audina Afriani; Muhamad Rizal; Sari Usih Natari (VISA: Journal of Vision and Ideas, 2023)
In connection with the dispute that occurs between the rights of overtime pay experienced by workers or laborers at PT. Tirta Investama Langkat Branch, workers are entitled to receive wages that should be received by workers but in the opinion of workers this has not been optimally fulfilled by the company. However, the company denied it and was of the view that so far they had optimized wages for their workers. Based on this phenomenon, the formulation of the problem in this study is (1) What is the background of the existence of disputes between employers and workers at PT. Tirta Investama Langkat which is connected with Law no. 2 of 2004?, (2) What is the process for resolving industrial relations disputes that occur between employers and workers at PT. Tirta Investama Langkat? This research used a normative juridical approach using a strategy based on the main legal materials by examining various concepts, theories, legal principles, and laws and regulations that have relevance to this research through research specifications, namely analytical descriptive. Primary and secondary law-based data sources adapted to laws and regulations and several books related to overtime pay rights through analysis of data use, namely analyzing qualitative data. The conclusions obtained from the research results of industrial relations dispute resolution processes are due to differences of opinion regarding overtime pay rights between workers and PT. Tirta Investama Langkat with settlement steps through a Bipartite process based on Law Number 2 of 2004 but did not obtain results, so it was continued with the Mediation stage with the mediator, namely the North Sumatra Provincial Employment Office. Keywords: industrial relations disputes, worker’s right, wages, mediation